Mengenalkan agama Sejak Dini untuk Pembentukan Karakter Anak Menurut Hindu di Era Globalisasi - I Made Sukancajaya; Ketut Nurhayanti; Ni Kadek Muliati (Indonesian Journal on Education (IJoEd), 2026)
The development of the times is marked by the rapid advancement of science and technology. These developments provide many conveniences for humans but on the other hand also bring negative impacts on the lives and younger generation of Hindus. Seeing such conditions, it is considered necessary to instill ethical teachings in the younger generation from an early age, starting with children. One of the negative impacts is the behavior of young people, such as a decline in morals and ethics due to adopting behaviors or habits from outside that do not align with cultural personality. Additionally, it can reduce interaction intensity because everything practical is done from home, thus erasing our character as Balinese people. who prioritize togetherness. Most Balinese people, who are predominantly Hindu, generally have several distinctive characteristics in their lives: they are highly religious and spiritual, always together or cooperative, friendly, polite and avoid conflict, creative and artistic, flexible, and strongly uphold traditions. Some values that need to be instilled in children from an early age are meant to be applied in their daily lives, such as: tri kaya parisudha, tat twam asi, the teachings of ahimsa, and the concept of karma phala. It is hoped that children will not only understand these teachings but also make them the foundation of Hindu personality in the future amidst modern times. Some ways to instill these teachings include: telling stories of goodness or, traditionally, doing it through Bali fairy tales/fables, then providing examples at home by parents and at school by teachers, and lastly instilling good habits or discipline in children.